2009
DOI: 10.1016/j.ejpain.2008.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid‐induced effects on the nociceptive system: A neurophysiological study in patients with secondary progressive multiple sclerosis

Abstract: Although clinical studies show that cannabinoids improve central pain in patients with multiple sclerosis (MS) neurophysiological studies are lacking to investigate whether they also suppress these patients' electrophysiological responses to noxious stimulation. The flexion reflex (FR) in humans is a widely used technique for assessing the pain threshold and for studying spinal and supraspinal pain pathways and the neurotransmitter system involved in pain control. In a randomized, double-blind, placebo-control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 64 publications
2
45
0
2
Order By: Relevance
“…In the present study, only ambulatory patients (EDSS \7) were included so as to minimize the negative contribution of musculoskeletal abnormalities on detection of CNS effects by active treatment. Conte and coworkers also failed to show changes in the H/M ratio following cannabinoid therapy in patients with secondary progressive MS [15]. Lack of significant effect of cannabis-based treatment on the H/M amplitude ratio was also reported in a limited sample of MS patients selected on the basis of neuropathic pain, not spasticity, without a placebo arm [14].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the present study, only ambulatory patients (EDSS \7) were included so as to minimize the negative contribution of musculoskeletal abnormalities on detection of CNS effects by active treatment. Conte and coworkers also failed to show changes in the H/M ratio following cannabinoid therapy in patients with secondary progressive MS [15]. Lack of significant effect of cannabis-based treatment on the H/M amplitude ratio was also reported in a limited sample of MS patients selected on the basis of neuropathic pain, not spasticity, without a placebo arm [14].…”
Section: Discussionmentioning
confidence: 94%
“…The Hoffmann (H) reflex is a neurophysiological measure of the efficiency of Iamotor neuron synaptic input related to spasticity [11,12]. Although the H-reflex has been reported to be reduced after baclofen treatment in MS patients [13], studies of Sativex have reported contrasting results [14,15].…”
Section: Introductionmentioning
confidence: 98%
“…It is thought to correspond to the pain threshold and the reflex size is related to the level of pain perception perception (Willer, 1977). In a randomized, doubleblind, placebo-controlled, cross-over study in 18 patients with secondary progressive MS, after treatment with Sativex, RIII reflex threshold increased and RIII reflex area decreased (Conte et al, 2009). The pain VAS also decreased, though not significantly.…”
Section: Sativex In Ms Neuropathic Painmentioning
confidence: 95%
“…Cannabinoid drugs such as delta-9-tetrahydrocannabinol (Δ 9 -THC) and cannabidiol have shown therapeutic potential in controlling MSassociated neurological disturbances including pain, spasticity, and mobility impairment [2] [3]. On the other hand, cannabis-based medications may also have a negative effect on symptoms associated with MS [4]. The effects or cannabis-based medicines are largely mediated through the activation of the cannabinoid receptors, CB 1 and CB 2 .…”
Section: Introductionmentioning
confidence: 99%